UJIAN SECARA ONLINE BAGI PENDIDIKAN TERBUKA DAN JARAK JAUH - Herman (LPPM Universitas Terbuka, 2010)
Open and Distance Learning (ODL) nowadays becomes a trend in higher education. Course delivery and course materials distribution have already been in electronic form by using information and communication technology (ICT). This technology becomes cheaper and much easier to be used. Indonesia as a nation where its people spread in thousands of islands does not always have face-to-face university in each city. Meanwhile, the need of skilled worker is always increased. ODL then becomes an alternative to educate people by using different way of teaching and learning process. People who have difficulties in accessing face-to-face university can use ODL as an alternative to upgrade their education. The role of ICT in ODL become important since the students can learn by using ICT. The students can also “meet” their colleagues virtually. Meanwhile, it was explored that ICT can be utilized for online examination. Online examination is more efficient, much faster in processing the examination result, and much cheaper in budget. This article discusses many aspects of strength and weakneses which is faced by educational institutions in administering online examinations.